2018
DOI: 10.1371/journal.pone.0203970
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of trainee dentists’ self-reported empathy and communication behaviors with simulated patients’ assessment in medical interviews

Abstract: ObjectivesWe aimed to clarify the communication behaviors between trainee dentists and simulated patients (SPs), to examine how the level of trainee dentists’ self-reported empathy influences assessment by SPs in medical interviews.Materials and methodsThe study involved 100 trainee dentists at Okayama University Hospital and eight SPs. The trainee dentists conducted initial interviews with the SPs after completing the Japanese version of the Jefferson Scale of Empathy (JSE). All interviews were recorded and a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 32 publications
3
20
0
1
Order By: Relevance
“…The decrease in the trainees' legitimizing and empathic communication may have prevented patients from raising concerns. This was consistent with our previous study [36]. However, considering the fact that total patient assessment has not declined, the effects of trainees' empathic attitudes may have a limited effect on SP satisfaction.…”
Section: Discussionsupporting
confidence: 92%
“…The decrease in the trainees' legitimizing and empathic communication may have prevented patients from raising concerns. This was consistent with our previous study [36]. However, considering the fact that total patient assessment has not declined, the effects of trainees' empathic attitudes may have a limited effect on SP satisfaction.…”
Section: Discussionsupporting
confidence: 92%
“…The decrease in the trainees' legitimizing and empathic communication may prevent patients from raising concerns. This is consistent with our previous study [34]. However, considering the fact that total patient assessment has not declined, the effects of trainees' empathic attitudes may have a limited effect on SP satisfaction.…”
Section: Discussionsupporting
confidence: 92%
“…Opposite findings originated from a recent international validation study employing a using a novel professionalism measurement tool for physicians and nurses, demonstrated a significant association between self-reported positive attitudes towards professionalism and participation in professionalism-linked behaviours including quality improvement initiatives [55]. Additionally, recent studies have identified significant correlations between self-reported empathy and quality of patient-centred communication in medical trainees [56], trainee dentists [57], and emergence medicine physicians [58]. The challenge of clarifying and characterizing the specific share of clinical empathy or professionalism captured by self-reported measures calls for further research.…”
Section: Discussionmentioning
confidence: 99%